2014
DOI: 10.2528/pierc13121307
|View full text |Cite
|
Sign up to set email alerts
|

Design and Characterization of a Dual-Band Metamaterial Absorber Based on Destructive Interferences

Abstract: Abstract-We present the design, characterization, and experimental verification of a dual-band metamaterial absorber (MA) in the microwave frequencies. The proposed MA consists of a metallic gammadion-shaped structure and a complete metal layer, separated by a dielectric spacer. The results show that the proposed MA has two absorption peaks at nearly 5.6 GHz and 6 GHz with absorption rates of 97% and 99%, respectively. The interference theory is used to investigate the physical mechanism of the proposed MA. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…In addition to the single band, dualband and multiband absorbers are reported by researchers. In line of this, Jamilan et al and Kaur et al, presented a dual‐band metamaterial absorber but the size of unit cell is extremely large. Moreover, absorber reported in Reference , fulfills the demand of compact size, however equivalent circuit modeling of the absorber for better insight of the design is not illustrated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the single band, dualband and multiband absorbers are reported by researchers. In line of this, Jamilan et al and Kaur et al, presented a dual‐band metamaterial absorber but the size of unit cell is extremely large. Moreover, absorber reported in Reference , fulfills the demand of compact size, however equivalent circuit modeling of the absorber for better insight of the design is not illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, equivalent circuit model of the proposed absorber is drawn with the help of surface current distributions and electric field distributions. The comparison between proposed absorber and other available designs in References are given in Table . From Table 1, it is confirmed that the proposed design in very prominent structure in terms of size, thickness, high peak absorption, and ease of fabrication.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, an ultra-thin fractal MA cell, first illustrated by the authors in Reference [9], is presented for dual-band operation within the UHF range. Even if other dual-band/multi-band MA configurations can be found in literature [10][11][12][13][14][15][16][17], this is the first example working at UHF frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike other multi-band MAs [10][11][12][13][14][15][16][17], the proposed fractal MA-cell allows to achieve closer absorbing peaks. Furthermore, the adopted single-layer structure offers reduced thickness ( λ/107) and very small unit cells ( 0.4λ), with λ being the free-space wavelength at the smaller resonant frequency.…”
Section: Introductionmentioning
confidence: 99%